Panel depicting Vaikuṇtha Vishnu image - Temples of India Project Team (Jio Institute, 2024)
The four faces of Vaikuṇtha Vishnu representants its four emanations or vyuha, namely Vasudeva, Sankarsana, Pradyumna and Aniruddha. The side faces are that of a boar and a lion, characteristic of Vaikuntha’s iconography. He is depicted seated in the lalitasana posture. The architectural fragment is now housed in the Government Museum, Sikar. This important image of Vaikuntha Vishnu reveals the presence of the Pancharatna form of Vaishnavism at Harsha hill. Pancharatna had spread to various regions of Rajasthan from the 8th century CE onwards, with its most notable manifestations in temples like the Harshatmata Temple of Abhaneri. This image signifies its influence, albeit in a limited manner, up to the region of Shekhavati. The niches on either side depict damsels and musicians. The four faces of Vaikuntha Vishnu representants its four emanations or vyuha, namely Vasudeva, Sankarsana, Pradyumna and Aniruddha. The side faces are that of a boar and a lion, characteristic of Vaikuṇtha’s iconography. He is depicted seated in the lalitasana posture.